EVALUATION OF TRADE EFFICIENCY IN SERBIA BASED ON DEA SUPER-RADIAL METHOD - Radojko (Poslovna ekonomija, 2023)
The issue of measuring and analyzing the dynamics of financial performance and trade efficiency is continuously current, significant and complex. Based on that, this paper measures and analyzes the financial performance and efficiency of trade in Serbia using the DEA ( Data Envelopment Analysis) Super-Radial model. According to the results of the Super-CCR-I model in the period 2002 -2021. trade in Serbia was not efficient in any year. And according to the results of the Super-CCR-O model, Serbia's trade in the period 2002 - 2021 was not efficient in any year. So, it was necessary to manage the analyzed input-output elements more efficiently. According to the obtained results of the Super-BCC-I model in the period 2002 - 2021, trade in Serbia was efficient in 2020 and 2021. Among other things, in other years it was ineffective due to poor management of the observed input - output elements. According to the results of the Super-BCC-O model, Serbia's trade in the period 2002 - 2021 was efficient in 2002 and 2015. In other years, among other things, due to inadequate management of the observed input - output elements, it was ineffective. In order to improve the financial performance and efficiency of trade in Serbia in the future, it is necessary, among other things, to manage input - output elements (human resources, assets, capital, sales and net profit) as efficiently as possible. Digitization of the entire business plays a significant role in this. Likewise, it is necessary to greatly mitigate the negative effects of the energy crisis.
Keywords: efficiency, factors, DEA Super-Radial models, Serbian trade